2009
DOI: 10.3310/hta13190
|View full text |Cite
|
Sign up to set email alerts
|

Dipsticks and diagnostic algorithms in urinary tract infection: development and validation, randomised trial, economic analysis, observational cohort and qualitative study

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 152 publications
2
100
1
1
Order By: Relevance
“…These findings are analogous to perceptions about prescriptions: GPs often perceive a pressure from patients to prescribe, investigate and refer despite the fact that patients do not report such expectations. 58 More recent findings from a qualitative study of patients attending with suspected urinary tract infection also identified patients' reluctance to rely on antibiotics to ameliorate symptoms, whereas GP interviews highlighted belief in patient pressure or desire for antibiotic prescriptions, 44,59 thus suggesting an ongoing disconnection between HCPs' views of patients' expectations and patients' expectations.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…These findings are analogous to perceptions about prescriptions: GPs often perceive a pressure from patients to prescribe, investigate and refer despite the fact that patients do not report such expectations. 58 More recent findings from a qualitative study of patients attending with suspected urinary tract infection also identified patients' reluctance to rely on antibiotics to ameliorate symptoms, whereas GP interviews highlighted belief in patient pressure or desire for antibiotic prescriptions, 44,59 thus suggesting an ongoing disconnection between HCPs' views of patients' expectations and patients' expectations.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…However, the variability of the performance of variables in these data sets -particularly striking for some variables such as cervical glands -suggests that such an approach is unlikely to provide the most valid method of variable selection for a clinical prediction rule, which is supported by similar findings in the development of clinical prediction rules for other acute infections. 44 The reason for this variation is unclear, but it may reflect varying infective agents, populations or clinician factors (e.g. reliability of history taking or examination).…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…The dipstick strategy is most likely to be cost-effective. 17 These criteria will also help to limit the unnecessary use of empiric antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…When nitrite, LE and blood are all negative the NPV for UTI has been shown to be 76 per cent (a quarter of patients would be told that they have no UTI when in fact they do). 11 The positive predictive value (PPV) of having a positive nitrite and either blood or LE result is approximately 92 per cent. A positive dipstick tests for nitrite and/or LE is less likely to predict bacteriuria than combinations of specific symptoms of dysuria and frequency without vaginal discharge (post-test probability of UTI: 81 per cent vs 96 per cent respectively).…”
Section: Near Patient Testingmentioning
confidence: 99%
“…LE, nitrite and blood are the important tests in evaluating for UTI. 11 The diagnostic accuracy of urine dipsticks for UTI varies with clinical setting and patient group. 12,13 Generally, a nitrite test is highly specific (96-99 per cent) but poorly sensitive (44-64 per cent).…”
Section: Near Patient Testingmentioning
confidence: 99%